Determination of Iron Content, Potassium, Calcium, and Sodium In Chinese Date Fruit (Ziziphus Jujuba Miller.) Fresh and Boiled In Atomic Adsorption Spectrophotometry - Nasution, Muhammad Amin; M, Masfria; Putra, Effendy De Lux (Asian Journal of Pharmaceutical Research and Development, 2022)
Chinese dates fruit are generally used by the people of Indonesia as a fruit that has a fairly good nutritional value, namely every 100 g of Chinese dates fruit contain 79 kcal of energy, 1.2 g protein, 20.23 g carbohydrates, 250 mg potassium, 21 mg calcium, 23 mg. phosphorus, 0.5 mg iron, 3 mg sodium, 10 mg magnesium, 0.1 vitamin B6 and 69 mg vitamin C. Chinese dates fruit are foods that are rich in fiber, so they can lower blood cholesterol and cure chronic constipation. In addition, Chinese dates fruit are foods with good sources of potassium. Adequate potassium intake can lower blood pressure so that it can reduce the risk of cardiovascular disease. High iron content can also prevent anemia. The purpose of this study was to determine the differences in the content of iron, potassium, calcium, and sodium in fresh and boiled Chinese dates fruit fruit, and to determine the percentage decrease in levels after boiling. The method used in this study included dry digestion, then quantitative analysis of iron, potassium, calcium, and sodium was carried out using the Atomic Absorption Spectrophotometry (AAS) method, namely iron at a wavelength of 248.3 nm, for potassium 766.5 nm, to calcium 422.7 nm, and sodium 589.0 nm. The results showed that the iron content in fresh Chinese dates fruit fruit was (0.6687 ± 0.0084) mg/100 g and boiled (0.3285 ± 0.0127) mg/100 g. Potassium levels in fresh Chinese dates fruit fruit (657.9024 ± 0.4713) mg/100 g and boiled (158.6504 ± 0.2510) mg/100 g. Calcium levels in fresh Chinese dates fruit fruit were (47.3501 ± 1.1630) mg/100 g and boiled (26.3968 ± 0.5922) mg/100 g, and sodium levels in fresh Chinese dates fruit fruit (16.1272 ± 0.1543) mg/100 g and boiled at (13.4048 ± 0.1973) mg/100 g. The percentage decrease in mineral content in Chinese dates fruit fruit after boiling, for iron was 50.87%, potassium 75.88%, calcium 44.25%; and 16.88% sodium. Statistically different test of the average mineral levels of iron, potassium, calcium, and sodium using the T distribution, it can be concluded that fresh Chinese dates fruit fruit contain higher levels of iron, potassium, calcium, and sodium minerals than boiled Chinese dates fruit.